Recent confirmed records of the Oncilla (Leopardus tigrinus) in the department of Antioquia, Colombia - Andrés Arias-Alzate; Juan D. Sánchez-Londoño; Sebastian Botero-Cañola; José F. González-Maya (Mammalogy Notes, 2014)
The oncilla or little spotted cat (Leopardus tigrinus) is the smallest and one of the more cryptic and little known wild felids species found in the Neotropics. Leopardus tigrinus has a discontinuous distribution from Costa Rica and Panamá, through Colombia and Ecuador in high elevation areas, with some records in the Cordillera of Mérida in Venezuela (evidence from three specimens from the NMNH) down to eastern Brazil, Bolivia and northern Argentina